Glacial and periglacial landforms and their recent dynamics in the Las Veguitas catchment, Cordillera Frontal of the Andes (Argentina) - Makopoulou, E.; Trombotto Liaudat, D.; Kuhry, P. (Frontiers in Earth Science, 2025)
The semi-arid Andes of South America are characterized by large areas with glacial and periglacial environments. This study focuses on the distribution and recent dynamics of glacial and periglacial landforms in the Las Veguitas catchment (3000–5500 m), Cordillera Frontal of the Andes, Argentina. A detailed geomorphological map of the catchment is presented, based on high-resolution elevation data (ALOS PALSAR), satellite imagery (WorldView 2), and field studies. First, a topographical analysis is performed for the entire Las Veguitas catchment, including elevation, slope and aspect characteristics. Second, the altitudinal range and predominant aspect of glacial features (perennial snow patches, debris-free glaciers, debris-covered glaciers and supraglacial lakes on debris-covered glaciers) and periglacial features (active, inactive and fossil rock glaciers) are analyzed. Currently, glaciers are restricted to ≥4,000 m, but moraines are identified to elevations of c. 3,200 m and lower. Active rock glaciers extend down to 3,350 m and have a more southern aspect than both inactive and fossil rock glaciers. Third, a temporal analysis of glacier and rock glacier flow in recent decades has been performed using a time series of remote sensing images. The average velocity of glacier flow of the debris-covered Vallecitos glacier is about 5.9 m/yr for the period 2006–2020. The mean velocity of the active part of two large rock glaciers is approximately 0.23 (Franke rock glacier) and 0.74 m/yr (Stepanek rock glacier) for the period 1962–2017.